Pengaruh Fasilitas Sekolah Terhadap Motivasi Belajar Siswa Kelas 5 SDN 1 Beluk Tahun Pelajaran 2023/2024 - Anggi Firnanda Putri; Nela Rofisian; Sri Suwartini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to determine the effect of school facilities on student learning motivation SDN 1 Beluk. This study discusses the effect of school facility to students` learning ability and motivation. Student creativity can be obtained in the learning process through various interactions and learning experiences and is based on the individual`s innate potential an environmental influences. The method in this research is ex post facto with a quantitative approach. The population in this study was class 5 of SDN 1 Beluk, totaling 99 students, however, due to limited funds, time and energy, in this study a sample of 20 students was used which was determined using the Proportional Random Sampling formula. The data collection technique uses a questionnaire regarding school facilities and student learning motivation. Research data analysis uses simple linear regression. The research results obtained have an impact on student learning facilities 43.0% school facilities are the most important factor due to the large.